A rare case report of acute necrotizing pancreatitis being the sole extra-pulmonary manifestation of COVID-19 - Kapardar, Bigyan Keshari; Pradhan, Soumya Ranjan (International Journal of Research in Medical Sciences, 2021)
The current pandemic of Corona virus disease (COVID) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Commonly the disease presents as symptoms suggestive of upper respiratory tract infection to severe acute respiratory infection syndrome (SARI). However various extra-pulmonary manifestations related to gastrointestinal system and hepatobiliary system including acute pancreatitis have been reported quite frequently. Here we report a case of COVID-19 who presented with acute necrotizing pancreatitis without any respiratory symptoms.